Negative Regulation of the Kinase LIN-45 By the E3/E4 Ubiquitin Ligase UFD-2 - (:unkn) unknown (My University, 2021)
The serine/threonine kinase BRAF is a key part of the Ras-Raf-MEK-ERK pathway, an inducer of cell growth, differentiation, and survival. In humans, activating mutations, most commonly BRAF(V600E), have been detected in several cancers, including melanoma and thyroid cancer. In the Caenorhabditis elegans ortholog LIN-45, the equivalent mutation LIN-45(V627E) results in elevated Raf-MEK-ERK signaling. We performed an unbiased genetic screen to identify negative regulators of LIN-45(V627E). Here, we report the identification of the E3/E4 ubiquitin ligase UFD-2, and show it is a negative regulator of LIN-45 protein activity and levels. Loss of UFD-2 leads to accumulation of wild-type LIN-45 protein as well as LIN-45(V627E). Based on analysis of truncations in the LIN-45 protein and mutations in the conserved 14-3-3 sites, we propose a model where UFD-2-dependent regulation requires binding by 14-3-3 proteins. This contrasts with the previously characterized degradation of LIN-45 by the E3 ubiquitin ligase SEL-10, which only requires a minimal phospho-degron sequence. We also identify the AAA ATPase CDC-48.1/2, a known interactor of UFD-2, as a negative regulator of LIN-45 protein stability. These findings represent a previously unrecognized mechanism of Ras-Raf-MEK-ERK regulation and will be the basis of future investigations of ubiquitin-mediated degradation of Raf.
Keywords: BRAF; development; ERK; melanoma; Ras; ubiquitination